(untitled) (Annual of the Faculty of Philosophy in Skopje, 2017)
The national security system in the Republic of China is in large scale determined by the specifics of the organization of the Chinese state, which is based on the historical development, and, also, from the need to build a new national security system, which will be in function to respond, respectively, to deal with the potential security threats toward the country. Analogically, the question is raised “ Whether the existing national security system is a rational assumption for achieving the goals of the national security policy?”, as well as the question “Whether China has adequate capacities for dealing with the security challenges?”; these issues are broadly set in the security agenda of the People ’s Republic of China and the necessary significance is constantly given in order to multiply the efforts for ensuring the peace and security of the country.